The determination of the ideas of the teachers in Turkey about the gifted students - ÖZDEMİR, AHMET ŞÜKRÜ (ELSEVIER SCIENCE BV, 2012)
Teachers play a great part of the education of gifted students (GS). The present research aimed to take the views of primary school teachers in Turkey about the GS. A view form was used. This form was prepared by researchers. This view form is answered by 139 (78 female, 61 male) teachers. The results show that the majority of teachers think that the classes and books are not suitable for GS and these students should be taken a different education. Also, the majority of the teachers think that the GS should't be in the same classes that normal students educating. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: Giftedness; the views of the teachers